Use Of Interactive Methods of Physicall Education Teachers (Journal of Pedagogical Inventions and Practices, 2024)
The purpose of the article is to substantiate cyclical matrix of the use of interactive teaching methods in the process of training future teachers physical culture. The article is devoted to the current problem of modernizing the professional training of future teachers of physical culture. Own observations and special studies in this regard indicate the need to systematize and implement interactive teaching methods. The author of the article reveals the possibilities of using case situations, sketch projects, research and heuristic games and functional trainings on the basic disciplines of the curriculum special attention in the work is paid to the activity approach, intensification and optimization of the training of future teachers physical culture, expansion of interdisciplinary connections